(3TQM Ydi GdRGjQLI GdSHJjI GdMhQLjIs - (3eLghds
(3ChdgG (B:s
(3GYde CjgG GdWGdH GdHGMKYf GdRGjQLI GdSHJjI EPG CQOJ GSJNQGL SDGd s
(3BNQgG (B:s
(3hGTcQ Gddg JYGdi Ydi eG ChdGc ef GdfYe hGdMeO dg QH GdYGdejf GfJgi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B52s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B(58) s
Keywords: (3GdMQha h GdChaGbs